Lactate-enhanced production of a cyclic β-1,2-glucan in Acetobacter pasteurianus - Yong Chen; Yihang Qi; Zhongya Zhou; Xin Liu; Yaping Sun; Ting Liu; Mengru Wu; Hui Li; Jing-yi Zhao; Zijun Xiao (Food Microbiology, 2027)

Evaluating ecological and socio-economic system dimensions to improve fisheries management in the Bohai Sea, China - Jie Yin; Jia Wo; Yunzhou Li; Ming Sun; Jacob G. Eurich; Kristin M. Kleisner; Shems B. Jud; Yi Tang; Shu Su; Yaping Ao; Yong Chen (Reviews in Fish Biology and Fisheries, 2026)

Tailoring MOF/PEO interface via self-assembled deep eutectic layer for advanced solid polymer electrolyte - Jing Li; Yifan Huang; Yaping Sun; Cheng Lian; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2026)

Orbital-hybridized electron bridge enables functional compartmentalization for ultradeep electrosorption - Bijie Bie; Xiaodong Xie; Shuncai Luo; Qingtan Xu; Song Xie; Yaping Miao; Xuming Zhang; Biao Gao; Zhaobo Wang; Buxiao Kuang; Fang Zhou; Liwei Xiong; et al. (Chemical Engineering Journal, 2026)

Metabolic engineering of Dunaliella salina enhances astaxanthin production: combined effects of heterologous enzyme co-expression and dual-stress optimization - Hao Zhang; Yifan Kong; Yaping Shao; Ziqi Zhang; Celong Zhao; Fuhao Xu; Fenglin Yang; Fengjie Sun; Yulin Cui; Yuyong Wu; Chunxiao Meng; Zhengquan Gao (World Journal of Microbiology and Biotechnology, 2026)

In situ generation of NKG2D CAR T/NK cells via a tumor-targeted lipoplex for enhancing cancer immunotherapy - Xiaoxuan Xu; Wenzhe Yi; Xiangshi Sun; Zhiwen Zhao; Jialin Duan; Ting Wu; Xiaoting Shan; Jie Li; Dangge Wang; Yaping Li (Science Bulletin, 2026)

Exploring contributions and responses of microbial quantity and diversity to coastal seasonal hypoxia - Guihao Li; Jiarong Hu; Pengfei Zheng; Ping Zhu; Yaping Wang; Songbao Zou; Xiaoli Zhang; Eleni Gentekaki; Song Sun; Aolin Zhu; Jun Gong (Marine Pollution Bulletin, 2026)

Iron-mediated reversal of humic acid inhibition in anoxygenic photoheterotrophic carbon fixation via redirected electron flux and restored redox homeostasis - Xiaoyan Bai; Ting Yu; Yaping Zhang; Jian Sun; Yong Yuan (Journal of Environmental Sciences, 2026)

Integrative metabolomic and genomic characterization of the high antimicrobial activity of Lacticaseibacillus paracasei and its potential for juice preservation - Fu Wei; Yanmei Sun; Yaping Mi; Chen Liang; Meichi Yue; Kehui Zhang; Rui Dong; Ziyi Zhang; Qiannan Yang; Songtao Guo; Shiwei Wang (Food Research International, 2026)

Seawater acidification accelerates growth but hastens decline in batch cultures of the marine diatom Thalassiosira pseudonana - Haiyang Zong; Zihao Sun; Dongmei Lv; Yu Shang; Yaping Wu; Juntian Xu; Futian Li (Marine Environmental Research, 2026)

Promoting the lattice oxygen mechanism via electronic modulation: Cobalt doping and heterointerface effects in RuO2@CuO for enhanced acidic oxygen evolution catalysis - Yuhe Zhang; Yuhui Sun; Yuchen Yang; Yaping Tang; Wei Jiang; Xianyu Chu; Chunbo Liu; jihui Lang; Yuanyuan Wu; Feifan Guo (Chemical Engineering Journal, 2026)

Changes of soil nematode communities affect the soil labile phosphorus under nitrogen addition in Pinus taiwanensis forests - Chenxing Lian; Qiufang Zhang; Xiaoqing Zhang; Mengli Liu; Quanxin Zeng; Yaping Lin; Jiaohong Lu; Hao Sun; Huizhi Pi; Mengxiao Ren; Xiaochun Yuan; Juyan Cui; et al. (Applied Soil Ecology, 2026)

Selective CO2 photoreduction to acetate enabled by charge-enriched interface sites confined in metal nanoclusters - Juncheng Zhu; Yang Wu; Jun Hu; Zijia Lin; Zexun Hu; Mingyu Wu; Runhua Chen; Kai Zheng; Wenxiu Liu; Bangwang Li; Junfa Zhu; Yang Pan; et al. (Science Bulletin, 2026)

Synergistic defense in cotton: Lignin-mediated barriers and JA/ET signaling pathways against Verticillium wilt - Zhixin Liu; Yinpeng Zhang; Yaping Zhou; Baozhen Wang; Jiani Long; Mengyu Liao; Xiaoli Fan; Wenxuan Kang; Beibei Liu; Xuwu Sun (Plant Science, 2026)

Characterization of Neomegalonema-dominated granulation in aerobic granules bioreactor: Evidence for stable filamentous granulation and quorum sensing-related activities - Lili Sun; Hanquan Wen; Lu Ding; Chao Qin; Mingxi Chen; Shike She; Xinchao Zhu; Jian Wang; Zengyang He; Yaping Zhang; Zhiqiang Xu; Quan Shu; et al. (Environmental Research, 2026)

Synthesis of borneol-based cationic copolymer microspheres via a dual strategy of stereochemistry and cationic sterilization for antibacterial coatings - Xiaobing Ma; Xiangbin Sun; Yuanyuan Xie; Rongmin Wang; Yaping Zhang; Yufeng He; Pengfei Song (Journal of Environmental Chemical Engineering, 2026)

Hydrogen bonding network induced by ambipolar small molecules facilitates high-performance all-solid-state Li batteries - Jing Li; Ruiqi Chai; Yaping Sun; Hengyi Wang; Cheng Lian; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2026)

Production of neofemales by 17β-estradiol and YY super-male breeding in northern snakehead (Channa argus) - Mi Ou; Yang Zhang; Rong Huang; Yaping Wang; Jianxiong Yin; Qing Luo; Kunci Chen; Haiyang Liu; Xincheng Zhang; Shuzhan Fei; Yuandong Sun; Baixiang Chen; et al. (Aquaculture, 2026)

Removal performance, molecular characteristics, and microbial mechanisms of dissolved organic nitrogen from secondary effluent in a pyrite-based autotrophic denitrification constructed wetland - Dong Wei; Yaping Sun; Xinwen Zhang; Shouqing Ni (Water Research, 2026)

Resveratrol can inhibit porcine reproductive and respiratory syndrome virus infection in vitro and in vivo by inhibiting PI3K/Akt signaling pathway - Yaping Chen; Wenshuang Chen; Xinqi Song; Xinyi Zhao; Li Yang; Ruoyu Zhao; Meilong Song; Bingbing Zhang; Dongbo Sun (Veterinary Microbiology, 2026)

Three-dimensional discrete fracture network identification based on deep learning and reversible jump Markov chain Monte Carlo algorithm - Zhenting Sun; Lei Ma; Quan Li; Yaping Deng; Han Qiu; Haichun Ma; Cihai Chen; Yongshuai Yan; Jiazhong Qian (International Journal of Rock Mechanics and Mining Sciences, 2026)

Electrically insulating BNNS/PVDF@AlN/PVP composites with simultaneously enhanced in-plane and through-plane thermal conductivities - Wei-Hua Han; Yaping Fan; Yu Long; Bin Sun; Yun-Ze Long; Chun-Cheng Hao (Chemical Engineering Journal, 2026)

Unveiling the stepwise catalysis of Ni Fe bimetallic single-atom sites toward high-efficiency lithium–sulfur batteries - Yaping Yan; Yi Yang; Zhihui Zhang; Changzheng Xin; Nan Yang; Tianwei He; Shude Liu; Zixu Sun; Yusuke Yamauchi; Ling Kang (Chemical Engineering Journal, 2025)

Impacts of nitrate on methane production and microbial communities in paddy soil - Wenjia Zhao; Lang Liu; Zhidong Liang; Jian Sun; Yi Wang; Hua Chen; Yaping Zhang; Yong Yuan (Journal of Soils and Sediments, 2025)

The dual-function of VN catalytic sites at cathode and anode toward high-performance lithium‑sulfur batteries - Yaping Yan; Yi Yang; Liu Yang; Xuefeng Luo; Guangzhao Wang; Qingquan Xue; Andreu Cabot; Hua Kun Liu; Shi Xue Dou; Zixu Sun (Chemical Engineering Journal, 2025)

Mo-Nitrogen nexus: Nanotechnology enhanced Mo-based nitrogen fixation towards environmental sustainability - Samina Irshad; Yu Xie; Yaping Lyu; Ziqi Zhang; Xingxin Liu; Haojie Wei; Beza Tuga; Christy L. Haynes; Yaqi Jiang; Yi Sun; Jason C. White; Yukui Rui; et al. (Chemical Engineering Journal, 2025)

Chemical composition and functional properties of protein-polyphenol complexes from purple rice: Effects of alkaline and enzymatic extraction - Yongchao Wang; Long Sun; Jianhong Peng; Zhengxuan Wang; Tianrui Zhao; Jianxin Cao; Yaping Liu; Guiguang Cheng; Charles Brennan (Food Chemistry, 2025)

Effect of labor migration on famers’ biopesticide application --mediating effect based on social network - Ruixin Zhang; Yexing Yin; Yushi Chen; Jinyang Sun; Yuying Liu; Xinhong Fu; Yaping Wang (Environment, Development and Sustainability, 2025)

Intensive oyster farming alters the microbial-regulated blue carbon storage in sediment - Xin Sun; Yihua Sun; Peilong Li; Yaping Gao; Ming Han; Peidong Zhang (Marine Pollution Bulletin, 2025)

Development and research progress of microalgae as a production platform for antimicrobial peptides - Qiaolei Wang; Yuyang Ma; Fengjie Sun; Kang Wang; Jinju Ma; Bingkui Zhu; Kai Cao; Yaping Shao; Yulin Cui; Hao Zhang; Yuyong Wu; Chunxiao Meng; et al. (Journal of Applied Phycology, 2025)

Enhanced nitrogen and phosphorus removal from actual domestic sewage using a novel ecological AAO process integrated with natural zeolite and vegetation - Zhiqiang Wang; Hua Chen; Jian Sun; Xingwen Lu; Yao He; Yujie Wang; Yaping Zhang; Renli Liang (Journal of Water Process Engineering, 2025)

Electrochemical enhancement of the accumulation of photosensitive components in anoxygenic phototrophic bacteria extracellular: A new insight into the preparation of degradable microbial photosensitizer for water treatment - Ronghui He; Jian Sun; Yong Yuan; Xiaoyan Bai; Qintie Lin; Yaping Zhang; Kang Dai; Zhenbo Xu (Journal of Hazardous Materials, 2025)

Role of Bacillus atrophaeus B1 in gut on nicotine tolerance of the fall armyworm - Yaping Chen; Wenyuan Zhao; Yanfang Hu; Yao Chen; Yahong Li; Zhongxiang Sun; Yuerui Li; Rongchao Luo; Ewei Du; Furong Gui (Pesticide Biochemistry and Physiology, 2025)

A dual-functional monomer-based molecularly imprinted fluorescent aptasensor employing near-infrared carbon dots for selective detection of quinine in food - Xuyuan Sun; Hao Liu; Zhengyuan Dai; Ying Wang; Li Li; Yaping Ding (Food Chemistry, 2025)

Quality differences in sea buckthorn (Hippophaë rhamnoides L.) berries of major varieties in China based on key components and antioxidant activity - Yaping Zheng; Kangmeng Sun; Xinyuan Sun; Yue Li; Peigen Xiao; Chunnian He (Food Chemistry, 2025)

Microplastics and Dechlorane Plus co-exposure amplifies their impacts on soybean plant - Yu Xie; Junzhe Zhang; Yaping Lyu; Yaqi Jiang; Yi Sun; Ziqi Zhang; Haojie Wei; Xingxin Liu; Yukui Rui; Wenlong Yang; Peng Zhang (Environmental Pollution, 2025)

How does high hydrostatic pressure treatment improve the esterification of quinoa (Chenopodium quinoa Willd.) starch? - Yaping Yin; Yongliang Zhuang; Liping Sun; Ying Gu; Gaopeng Zhang; Xuejing Fan; Yangyue Ding (Food Chemistry, 2025)

A flexible humidity-resistant nanofiber-based triboelectric nanogenerator with high electrical output stability as self-powered sensors for motion monitoring - Yue Sun; Zicheng Qian; Yuna Wang; Yaping Li; Yide Zheng; Yong Liu (Chemical Engineering Journal, 2025)

An ultrathin conformal layer of dry-coated Li+-conductive glass–ceramic for single-crystalline nickel-rich cathode towards all-solid-state lithium batteries - Yaping Wang; Jianxiang Ding; Xiong Xiong Liu; Mufan Cao; Min Gao; Long Pan; ZhengMing Sun (Chemical Engineering Journal, 2025)

Foreign directors and corporate social responsibility reporting in China: the moderating role of institutional pressures - Weizhang Sun; Yi Lu; Yifei Zhang; Yaping Wang; Zhizhong Xue (Environment, Development and Sustainability, 2024)

Enhanced reductive catalytic fractionation of lignocellulose using a water-resistant RuNiZnOx/Nb2O5 catalyst with synergistic hydrogen spillover and acidic properties - Zhaozhuo Yu; Wenzhuo Kong; Yaping Guo; Wen Liang; Jiawei Liang; Meijuan Chen; Dongxu Zhao; Hongzhen Ma; Xiangjun Liu; Solomon Inalegwu Okopi; Lei Che; Qi Zhang; et al. (Fuel, 2024)

Angelica sinensis polysaccharides promote extramedullary stress erythropoiesis via ameliorating splenic glycolysis and EPO/STAT5 signaling-regulated macrophages - Nianci Sun; Ziling Wang; Honghui Jiang; Biyao Wang; Kunhang Du; Caihong Huang; Cheng Wang; Ting Yang; Yaping Wang; Yafei Liu; Lu Wang (Journal of Molecular Histology, 2024)

Synthesis of P-Rich Carbon Quantum Dots for Sensitive Fluorescent Detection of 2-Methylimidazole - Zhengyuan Dai; Hao Liu; Xuyuan Sun; Ying Wang; Jie Fan; Li Li; Yaping Ding (Journal of Fluorescence, 2024)

Effect of maternal cigarette smoke exposure on COPD progression in offspring mice - Jiawei Sun; Huan Chen; Xu Xu; Yaping Dou; Baofa Wu; Hongyang Zhang; Song Shang; Wuzhuang Sun (Reproductive Toxicology, 2024)

Regulation of nitrogen metabolism by COE2 under low sulfur stress in Arabidopsis - Vincent Ninkuu; Yaping Zhou; Hao Liu; Susu Sun; Zhixin Liu; Yumeng Liu; Jincheng Yang; Mengke Hu; Liping Guan; Xuwu Sun (Plant Science, 2024)

Role of Enterococcus mundtii in gut of the tomato leaf miner (Tuta absoluta) to detoxification of Chlorantraniliprole - Yao Chen; Yaping Chen; Yibo Zhang; Zhongxiang Sun; Yahong Li; Jiasheng Ding; Guifen Zhang; Ewei Du; Xiaoyan Zi; Chaoxin Tian; Wenyuan Zhao; Furong Gui (Pesticide Biochemistry and Physiology, 2024)

Biochar with KMnO4-hematite modification promoted foxtail millet growth by alleviating soil Cd and Zn biotoxicity - Xirui Kang; Na Geng; Yaping Li; Wei He; Hui Wang; Hong Pan; Quangang Yang; Zhongchen Yang; Yajie Sun; Yanhong Lou; Yuping Zhuge (Journal of Hazardous Materials, 2024)

Comprehensive comparison of integrated fixed-film activated sludge (IFAS) and AAO activated sludge methods: Influence of different operational parameters - Zihua Lan; Yaping Zhang; Renli Liang; Zhiqiang Wang; Jian Sun; Xingwen Lu; Yao He; Yujie Wang (Chemosphere, 2024)

Effect of complex prebiotics on Lactobacillus gasseri JM1 fermented soymilk: Physicochemical, flavor characteristics, and metabolites - Yaping Zheng; Wenfang Wu; Man Zhu; Yilin Sun; Dong Hu; Yujun Jiang; Yu Zhang; Chaoxin Man (Food Bioscience, 2024)

Biological functions of active ingredients in quinoa bran: Advance and prospective - Feiyan Yang; Tianyi Guo; Yaping Zhou; Shuai Han; Shuguo Sun; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2024)

An Advanced Molecularly Imprinted Photochemical Sensor Based Carbon Quantum dots for Highly Sensitive Detection of Chloramphenicol in Food - Hao Liu; Jing Yang; Xuyuan Sun; Peijie Wu; Guan Wang; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2024)

Photochemical behaviors of sludge extracellular polymeric substances from bio-treated effluents towards antibiotic degradation: Distinguish the main photosensitive active component and its environmental implication - Xuexian Zhong; Jian Sun; Yong Yuan; Yaping Zhang; Xiaoyan Bai; Qintie Lin; Kang Dai; Zhenbo Xu (Journal of Hazardous Materials, 2024)

A novel alginate-embedded magnetic biochar-anoxygenic photosynthetic bacteria composite microspheres for multipollutant removal: Mechanisms of photo-bioelectrochemical enhancement and excellent reusability performance - Ronghui He; Jian Sun; Xiaoyan Bai; Qintie Lin; Yong Yuan; Yaping Zhang; Kang Dai; Zhenbo Xu (Environmental Research, 2024)

Description of Microbacterium dauci sp. nov., a plant growth hormone indoleacetic acid-producing and nitrogen-fixing bacterium isolated from carrot rhizosphere soil - Jiawen Zheng; Yunyu Liao; Yang Li; Dongsheng Li; Yaping Sun; Zijun Xiao (Archives of Microbiology, 2024)

Identification of high-permeability and water-rich zones in a fractured karst water source area based on the hydraulic tomography method - Lei Ma; Xiaofan Sun; Jiazhong Qian; Wei Wang; Yaping Deng; Yunhai Fang (Journal of Hydrology, 2024)

Engineered nanomaterials display a variable interaction with anoxygenic photoelectrogenic biofilm for pharmaceutical pollutants degradation - Ronghui He; Xubin Zhang; Jian Sun; Xiaoyan Bai; Qintie Lin; Yong Yuan; Yaping Zhang; Kang Dai; Zhenbo Xu (Chemical Engineering Journal, 2024)

Characteristics and mechanism of phosphate removal by lanthanum modified bentonite in the presence of dissolved organic matter - Mingxin Zhang; Yaping Zhang; Xi Chen; Jian Sun; Xingwen Lu; Yao He; Yujie Wang (Chemosphere, 2023)

Photo-aged non-biodegradable and biodegradable mulching film microplastics alter the interfacial behaviors between agricultural soil and inorganic arsenic - Shuai Tang; Peipei Sun; Guojuan Qu; Yue Tian; Junlai Liu; Md. Nahid Pervez; Xiuyan Li; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2023)

Dual-emitting cellulose nanocrystal hybrid materials with circularly polarized luminescence for anti-counterfeiting labels - Lingxiao Xing; Guihua Li; Yaping Sun; Xu Wang; Zaiwu Yuan; Yingjuan Fu; Menghua Qin (Carbohydrate Polymers, 2023)

Uncovering the dynamic evolution of microbes and n-alkanes: Insights from the Kuroshio Extension in the Northwest Pacific Ocean - Xin Hu; Xinping Wang; Shanshan Zhao; Lixin Cao; Yaping Pan; Fujuan Li; Fengshu Li; Jinren Lu; Yiming Li; Guodong Song; Honghai Zhang; Peiyan Sun; et al. (Science of The Total Environment, 2023)

A mechanically soft-tissue-like organohydrogel with multi-functionalities for sensitive soft ionotronics - Shuxiang Liu; Yuping Chen; Jin Feng; Junjie Peng; Yaping Zhou; Yang Zhao; Yongpeng Zhao; Zhiwei Lu; Mengmeng Sun; Chun Wu; Haipeng Hu; Hanbing Rao; et al. (Chemical Engineering Journal, 2023)

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

Single atomic ruthenium in WO3 boosted hydrogen evolution stability at Ampere-level current density in whole pH range - Hai Liu; Guoying Tan; Mengxuan Li; Zhuang Zhang; Marshet Getaye Sendeku; Yaping Li; Yun Kuang; Xiaoming Sun (Chemical Engineering Journal, 2023)

Disruption of phosphate metabolism and sterol transport-related genes conferring yeast resistance to vanillin and rapid ethanol production - Fengguang Zhao; Yaping Zhang; Jian Hu; Ce Shi; Xiang Ao; Shengding Wang; Ying Lin; Zhongwei Sun; Shuangyan Han (Bioresource Technology, 2023)

UFM1 inhibits the activation of the pyroptosis in LPS-induced goat endometritis - Zongjie Wang; Shan Huang; Zhongqiang Xue; Kangkang Gao; Min Sun; Aihua Wang; Pengfei Lin; Yaping Jin (Theriogenology, 2023)

The interfacial behaviors of different arsenic species on polyethylene mulching film microplastics: Roles of the plastic additives - Shuai Tang; Peipei Sun; Shengjia Ma; Wei Jin; Yaping Zhao (Journal of Hazardous Materials, 2023)

A high-efficiency mixotrophic photoelectroactive biofilm reactor (MPBR) for enhanced simultaneous removal of nutrients and antibiotics by integrating light intensity regulation and microbial extracellular electron extraction - Xinyuan Yao; Jian Sun; Xiaoyan Bai; Yong Yuan; Yaping Zhang; Yanbin Xu; Guofu Huang (Journal of Environmental Management, 2023)

Experimental study on the treatment of desulfurization wastewater from coal-fired power plant by spray evaporation - Zongkang Sun; Ning Zhao; Yongxin Feng; Fengjun Liu; Chenjian Cai; Guangmin Che; Yaping Zhang; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Transcriptome Analysis Reveals Differential Gene Expression in Garlic Aerial Bulbs in Response to Gibberellin Application - Yuhui Dong; Hongcheng Fang; Yujiao Hou; Yaping Zhao; Xiudong Sun; Shiqi Liu (Journal of Plant Growth Regulation, 2022)

Urolithin A inhibits enterovirus 71 replication and promotes autophagy and apoptosis of infected cells in vitro - Shengyu Wang; Junhua Qiao; Yaping Chen; Langfei Tian; Xin Sun (Archives of Virology, 2022)

Carbon footprint analysis of straw collection, transportation, and storage system for power generation in China based on emergy evaluation - Yufeng Sun; Bin Yang; Yapeng Wang; Zipeng Zheng; Jinwei Wang; Yaping Yue; Wenlong Mu (Environmental Science and Pollution Research, 2022)

Soil phosphorus availability and stoichiometry determine microbial activity and functional diversity of fluvo-aquic soils under long-term fertilization regimes - Wei He; Wenhua Ye; Mingjie Sun; Yaping Li; Manman Chen; Meng Wei; Guoqing Hu; Quangang Yang; Hong Pan; Yanhong Lou; Hui Wang; Yuping Zhuge (Journal of Soils and Sediments, 2022)

Changes in Transcriptome and Ultrastructure Reveal Salinity Tolerance of Obscure Puffer Takifugu obscurus - Jun Wang; Xuexia Zhu; Yunfei Sun; Lei Gu; Yaping Wu; Yafen Chen; Zhou Yang (Frontiers in Marine Science, 2022)
Fish can maintain a stable intracellular concentration of ions in environments of variable salinities through osmoregulation. In this study, we focused on obscure puffer Takifugu obscurus ( T. obscurus ), an anadromous fish with high commercial value and rapid depression of wide populations, to investigate changes at molecular and physiological levels underlying salinity tolerance through multifaceted analyses integrating transcriptomics and micrography. We found that with the increase of salinity, the structure of the three main osmoregulation organs, i.e., gill, intestine, and kidney had remarkable changes. The results of transcriptome demonstrated that the ATP-binding box transporter and cyclic adenosine monophosphate (cAMP) signaling pathway in the gill and kidney were significantly reduced. Growth hormone, prolactin, and cortisol regulated more transporters of body composition and stimulated chloride cell proliferation and differentiation, which change the capacity for membrane transport between ion and water molecules. Adenosine-activating protein kinase and thyroid hormone signaling pathway were also significantly upregulated. These transcriptional levels changes of T. obscurus combined with ultrastructure in response to salinity increase indicated that osmoregulation is a complex process involving multiple organs and signaling pathways. Overall, this study can deepen the understanding of osmotic regulation during fish migration.

Spatio-temporal analysis of urban air pollutants throughout China during 2014–2019 - Chenkai Zhao; Ying Sun; Yaping Zhong; Senhao Xu; Yue Liang; Shu Liu; Xiaodong He; Jinghai Zhu; Takayuki Shibamoto; Miao He (Air Quality, Atmosphere & Health, 2021)

Cotton seedling drought tolerance is improved via salt preconditioning - Rong Fan; Xiujuan Su; Yaping Guo; Fenglei Sun; Yanying Qu; Quanjia Chen (Protoplasma, 2021)

The Beneficial Effects of Aluminum on the Plant Growth in Camellia japonica - Yuanjiao Liu; Jingyu Tao; Jing Cao; Yaping Zeng; Xi Li; Jun Ma; Zhuo Huang; Mingyan Jiang; Lingxia Sun (Journal of Soil Science and Plant Nutrition, 2020)

Could urinary ACE2 protein level help identify individuals susceptible to SARS-CoV-2 infection and complication? - Xiaotian Ni; Changqing Sun; Yaping Tian; Yanjie Huang; Tongqing Gong; Lan Song; Xing Yang; Kai Li; Nairen Zheng; Jianping Wang; Hongxing Wu; Ruoxian Zhang; et al. (Science China Life Sciences, 2020)

Gene UCHL1 expresses specifically in mouse uterine decidual cells in response to estrogen - Lishuang Hao; Di Song; Mengfei Zhuang; Yan Shi; Lin Yu; Yaping He; Jian Wang; Tingting Zhang; Zhaogui Sun (Histochemistry and Cell Biology, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Cloud type identification for a landfalling typhoon based on millimeter-wave radar range-height-indicator data - Zhoujie Cheng; Ming Wei; Yaping Zhu; Jie Bai; Xiaoguang Sun; Li Gao (Frontiers of Earth Science, 2019)

Effect of ionic liquid [MIm]HSO4 on WPCB metal-enriched scraps refined by slurry electrolysis - Yaping Qi; Xiaoxia Yi; Yugai Zhang; Fansong Meng; Jiancheng Shu; Furong Xiu; Zhi Sun; Shuhui Sun; Mengjun Chen (Environmental Science and Pollution Research, 2019)

Myelin Oligodendrocyte Glycoprotein-IgG Contributes to Oligodendrocytopathy in the Presence of Complement, Distinct from Astrocytopathy Induced by AQP4-IgG - Ling Fang; Xinmei Kang; Zhen Wang; Shisi Wang; Jingqi Wang; Yifan Zhou; Chen Chen; Xiaobo Sun; Yaping Yan; Allan G. Kermode; Lisheng Peng; Wei Qiu (Neuroscience Bulletin, 2019)

Delineation of contaminant plume for an inorganic contaminated site using electrical resistivity tomography: comparison with direct-push technique - Qing Liao; Yaping Deng; Xiaoqing Shi; Yuanyuan Sun; Weidong Duan; Jichun Wu (Environmental Monitoring and Assessment, 2018)

Molecular cytogenetic and genomic analyses reveal new insights into the origin of the wheat B genome - Wei Zhang; Mingyi Zhang; Xianwen Zhu; Yaping Cao; Qing Sun; Guojia Ma; Shiaoman Chao; Changhui Yan; Steven S. Xu; Xiwen Cai (Theoretical and Applied Genetics, 2018)

Three new oleanane-type triterpenoid saponins from the seeds of Celosia cristata L. - Xin Liu; Jifa Zhang; Kai Guo; Airong Jia; Miansong Zhang; Yaping Shi; Changheng Liu; Linlin Xiao; Zhenliang Sun (Natural Product Research, 2018)

Water and CO2 fluxes over semiarid alpine steppe and humid alpine meadow ecosystems on the Tibetan Plateau - Lei Wang; Huizhi Liu; Yaping Shao; Yang Liu; Jihua Sun (Theoretical and Applied Climatology, 2018)

A Brachypodium distachyon MAPKK Gene BdMKK6.2 Negatively Regulates Drought Stress Tolerance in Transgenic Tobacco Plants - Jiutong Sun; Run Zhou; Yaping Li; Wei Hu; Ding Qiu; Xiatian Wang; Qiong Wang; Zhijuan Feng; Lianzhe Wang; Yi Zhou; Guangyuan He; Guangxiao Yang (Journal of Plant Growth Regulation, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Tamlana nanhaiensis sp. nov., isolated from surface seawater collected from the South China Sea - Xiupian Liu; Qiliang Lai; Yaping Du; Guangyu Li; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

A recombinant canine distemper virus expressing a modified rabies virus glycoprotein induces immune responses in mice - Zhili Li; Jigui Wang; Daoli Yuan; Shuang Wang; Jiazeng Sun; Bao Yi; Qiang Hou; Yaping Mao; Weiquan Liu (Virus Genes, 2015)

Tamlana nanhaiensis sp. nov., isolated from surface seawater collected from the South China Sea - Xiupian Liu; Qiliang Lai; Yaping Du; Guangyu Li; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Pseudooceanicola atlanticus gen. nov. sp. nov., isolated from surface seawater of the Atlantic Ocean and reclassification of Oceanicola batsensis, Oceanicola marinus, Oceanicola nitratireducens, Oceanicola nanhaiensis, Oceanicola antarcticus and Oceanicola flagellatus, as Pseudooceanicola batsensis comb. nov., Pseudooceanicola marinus comb. nov., Pseudooceanicola nitratireducens comb. nov., Pseudooceanicola nanhaiensis comb. nov., Pseudooceanicola antarcticus comb. nov., and Pseudooceanicola flagellatus comb. nov. - Qiliang Lai; Guizhen Li; Xiupian Liu; Yaping Du; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Emcibacter nanhaiensis gen. nov. sp. nov., isolated from sediment of the South China Sea - Xiupian Liu; Guangyu Li; Qiliang Lai; Fengqin Sun; Yaping Du; Zongze Shao (Antonie van Leeuwenhoek, 2015)

Idiomarina atlantica sp. nov., a marine bacterium isolated from the deep sea sediment of the North Atlantic Ocean - Juan Du; Qiliang Lai; Yang Liu; Yaping Du; Xiupian Liu; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

The Brachypodium distachyon BdWRKY36 gene confers tolerance to drought stress in transgenic tobacco plants - Jiutong Sun; Wei Hu; Run Zhou; Lianzhe Wang; Xiatian Wang; Qiong Wang; Zhijuan Feng; Yaping Li; Ding Qiu; Guangyuan He; Guangxiao Yang (Plant Cell Reports, 2015)

FLT3 and CDK4/6 inhibitors: Signaling mechanisms and tumor burden in subcutaneous and orthotopic mouse models of acute myeloid leukemia - Yaping Zhang; Cheng-Pang Hsu; Jian-Feng Lu; Mita Kuchimanchi; Yu-Nien Sun; Ji Ma; Guifen Xu; Yilong Zhang; Yang Xu; Margaret Weidner; Justin Huard; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

A PCR-based microwell-plate hybrid capture assay for high-risk human papillomavirus - Yumei Wang; Yan Liu; Yaping Ding; Nan Sun; Yafang Gong; Shangxian Gao (Archives of Virology, 2014)

Actibacterium atlanticum sp. nov., isolated from surface seawater of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Fengqin Sun; Yaping Du; Xiupian Liu; Guangyu Li; Yunbiao Xie; Zongze Shao (Antonie van Leeuwenhoek, 2014)

Aquimarina atlantica sp. nov., isolated from surface seawater of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Fengqin Sun; Xiupian Liu; Yunbiao Xie; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2014)

GRP78 expression and regulation in the mouse uterus during embryo implantation - PengFei Lin; YaPing Jin; XiangLi Lan; YanZhou Yang; Fenglei Chen; Nan Wang; Xiao Li; YuJie Sun; AiHua Wang (Journal of Molecular Histology, 2014)

Erratum to: Maricoccus atlantica gen. nov. sp. nov., isolated from deep sea sediment of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Xiupian Liu; Fengqin Sun; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2014)

Maricoccus atlantica gen. nov. sp. nov., isolated from deep sea sediment of the Atlantic Ocean - Guizhen Li; Qiliang Lai; Xiupian Liu; Fengqin Sun; Yaping Du; Guangyu Li; Zongze Shao (Antonie van Leeuwenhoek, 2013)

Gender Differences in Preattentive Processing of Facial Expressions: An ERP Study - Qiang Xu; Yaping Yang; Pei Wang; Gang Sun; Lun Zhao (Brain Topography, 2013)

Comparative proteomic analysis of the H99 inbred maize (Zea mays L.) line in embryogenic and non-embryogenic callus during somatic embryogenesis - Lifang Sun; Ying Wu; Hongda Zou; Shengzhong Su; Shipeng Li; Xiaohui Shan; Jinghui Xi; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Antigenic analysis of grass carp reovirus using single-chain variable fragment antibody against IgM from Ctenopharyngodon idella - CongLin Chen; XiaoYun Sun; LanJie Liao; ShaoXiang Luo; ZhouQuan Li; XiaoHua Zhang; YaPing Wang; QionLin Guo; Qin Fang; HePing Dai (Science China Life Sciences, 2013)

Enlargement of anode for enhanced simultaneous azo dye decolorization and power output in air-cathode microbial fuel cell - Jian Sun; Youming Li; Yongyou Hu; Bin Hou; Qian Xu; Yaping Zhang; Sizhe Li (Biotechnology Letters, 2012)

Differential gene expression during somatic embryogenesis in the maize (Zea mays L.) inbred line H99 - Lifang Sun; Ying Wu; Shengzhong Su; Hongkui Liu; Guang Yang; Shipeng Li; Xiaohui Shan; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Synergistic or Antagonistic Effect of MTE plus TF or Icariin from Epimedium koreanum on the Proliferation and Differentiation of Primary Osteoblasts In Vitro - Jinchao Zhang; Yaping Li; Jing Sun; Cuilian Liu; Dawei Zhang (Biological Trace Element Research, 2011)

Effects of exogenous glutathione on arsenic burden and NO metabolism in brain of mice exposed to arsenite through drinking water - Yan Wang; Fenghong Zhao; Yaping Jin; Yuan Zhong; Xiaoyun Yu; Gexin Li; Xiuqiang Lv; Guifan Sun (Archives of Toxicology, 2011)

Distribution and Speciation of Arsenic by Transplacental and Early Life Exposure to Inorganic Arsenic in Offspring Rats - Shuhua Xi; Yaping Jin; Xiuqiang Lv; Guifan Sun (Biological Trace Element Research, 2010)

Identification and characterization of HTD2: a novel gene negatively regulating tiller bud outgrowth in rice - Wenzhen Liu; Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Weijiang Luan; Zhengquan He; Zongxiu Sun (Planta, 2009)

The Polymorphism of DNA Repair Gene ERCC2/XPD Arg156Arg and Susceptibility to Breast Cancer in a Chinese Population - Jiaoyang Yin; Duohong Liang; Ulla Vogel; Yaping Chang; Zhengrong Liu; Li Yue; Xiaoling Sun; Rong Qi; Tiehua Song (Biochemical Genetics, 2009)

Transplacental and early life exposure to inorganic arsenic affected development and behavior in offspring rats - Shuhua Xi; Wenjuan Sun; Fengzhi Wang; Yaping Jin; Guifan Sun (Archives of Toxicology, 2009)

Urinary Arsenic Speciation and its Correlation with 8-OHdG in Chinese Residents Exposed to Arsenic Through Coal Burning - Xin Li; Jingbo Pi; Bing Li; Yuanyuan Xu; Yaping Jin; Guifan Sun (Bulletin of Environmental Contamination and Toxicology, 2008)

Identification and fine mapping of a thermo-sensitive chlorophyll deficient mutant in rice (Oryza sativa L.) - Wenzhen Liu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Chao Wu; Zongxiu Sun (Planta, 2007)